Clinical Character of CASPR2 Autoimmune Encephalitis: A Multiple Center Retrospective Study - Qin, Xiaoxiao; Yang, Huajun; Zhu, Fei; Wang, Qun; Shan, Wei (Frontiers in Immunology, 2021)
Objective To examine the clinical characteristics of autoimmune encephalitis associated with the contactin-associated protein-2 (CASPR2) antibody. Materials and Methods Medical records of all patients diagnosed with CASPR2 antibody-associated encephalitis were retrospectively analysed. Data regarding demographic features, neurological symptoms and signs, laboratory tests, imaging results, treatments, and prognosis were collected. Results A total of 25 patients aged from 3 to 79 years old were enrolled in this study, with a median age of 43. Eight of 25 (32%) were female, and 17 of 25 (68%) were male. The median age of symptom onset was 42 years old with the course of disease from onset to hospital admission ranging from 2 days to 6 months (median was 17 days). Six patients (6/25) had fever as an onset symptom. During the course of disease, cognitive disturbance was the most common symptom, which was observed in 17 patients (17/25) in total. Eight patients (8/25) met the criteria for limbic encephalitis. Epileptic seizure occurred in six of these eight patients. Four patients (4/25) were diagnosed as Morvan syndrome. All patients were positive for anti-CASPR2 antibody in the serum (1:10–1:300). In six patients, antibodies were detected both in the blood and CSF (1:32–1:100). White blood cell (WBC) counts in the CSF were elevated in eight patients (8/25). The concentration of proteins in CSF increased in 10 patients (ranging from 480 to 1,337.6 mg/dl), decreased in seven patients (ranging from 23.2 to 130.5 mg/dl) and remained at a normal range in the other eight patients (ranging from 150 to 450 mg/dl). Abnormal electroencephalogram (EEG) activities included slow background activity and epileptic patterns. Abnormal signals in the bilateral hippocampus were detected by magnetic resonance imaging (MRI) in three patients presenting cognitive disturbance. In one patient who had limbic encephalitis, increased metabolism of bilateral basal ganglia and the mesial temporal lobe was revealed by PET-CT. Eleven of 15 patients receiving immunotherapy experienced varying degrees of improvement. Relapse occurred in four of 25 patients (4/25) after 2 months. Conclusion CASPR-antibody-mediated autoimmune encephalitis is characterized by diverse clinical manifestations. The most prominent conclusion revealed by this retrospective analysis is the involvement of both central and peripheral nerve systems, as well as a lower relapse rate, a good response to immunotherapy, and favorable short-term prognosis after treatment was also demonstrated. Besides, additional work is necessary to evaluate the long-term prognosis.